2013
DOI: 10.5944/educxx1.16.1.725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación De Un Programa De Educación Emocional Para Profesorado De Primaria (Evaluation of an Emotional Education Program for Primary Teachers)

Abstract: RESUMENEn este trabajo se presenta la evaluación de un programa de educación emocional dirigido a profesores de educación primaria, mediante una investigación cuasi-experimental pre-test post-test con grupo control. Participaron de la experiencia 92 profesores de tres centros educativos de Barcelona y Lleida. El programa incidió en el desarrollo de las cinco dimensiones de la competencia emocional siguiendo el modelo de Bisquerra y Pérez (2007): conciencia, regulación, autonomía, competencia social y competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
26

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 6 publications
0
5
0
26
Order By: Relevance
“…For the elaboration of ICMC, conceptual proposals have been analyzed (e.g., Hauser, 2019), empirical studies of psychopedagogical intervention in emotional education and experience sampling, applied in the field of education (e.g., P.E.C.E.R.A., by de Morales Ibáñez and Alzina, 2006; The Evaluation of the Program for the Prevention of Structural Violence in the Family and School Centers, of Moral and Pérez, 2010;Happy Emotional Education Program, of Filella et al, 2018), as well as models and theories that deal with the central elements separately (e.g., Murray, 2005;Caballero, 2010;Cabanach et al, 2010;Pérez-Escoda et al, 2013;Romera et al, 2015;Balzarotti et al, 2016;Filella et al, 2016, among others); this analysis has indicated three possible areas of conflict development that should be considered; in the first place, the conflict that the person has with himself (from the theory of the psychic apparatus, Salcedo, 2010); second, the conflict that the person has with another person (from Darwin's theory of evolution, Aznavurian, 2012) and, finally, the conflict that is generated between groups (from Marx's class conflict theory, Izaguirre, 2014). We consider that analyzing this oscillation between the "I" and the "we, " between the being as an individual entity and the being as a social entity, with the mediation of exercises that encourage creativity, imagination, reflection and the development of consciousness, it enables the execution of cognitive reevaluation and, therefore, the development of the ability to alter one's responses, one of the characteristics associated with the human condition (Baumeister and Heatherton, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For the elaboration of ICMC, conceptual proposals have been analyzed (e.g., Hauser, 2019), empirical studies of psychopedagogical intervention in emotional education and experience sampling, applied in the field of education (e.g., P.E.C.E.R.A., by de Morales Ibáñez and Alzina, 2006; The Evaluation of the Program for the Prevention of Structural Violence in the Family and School Centers, of Moral and Pérez, 2010;Happy Emotional Education Program, of Filella et al, 2018), as well as models and theories that deal with the central elements separately (e.g., Murray, 2005;Caballero, 2010;Cabanach et al, 2010;Pérez-Escoda et al, 2013;Romera et al, 2015;Balzarotti et al, 2016;Filella et al, 2016, among others); this analysis has indicated three possible areas of conflict development that should be considered; in the first place, the conflict that the person has with himself (from the theory of the psychic apparatus, Salcedo, 2010); second, the conflict that the person has with another person (from Darwin's theory of evolution, Aznavurian, 2012) and, finally, the conflict that is generated between groups (from Marx's class conflict theory, Izaguirre, 2014). We consider that analyzing this oscillation between the "I" and the "we, " between the being as an individual entity and the being as a social entity, with the mediation of exercises that encourage creativity, imagination, reflection and the development of consciousness, it enables the execution of cognitive reevaluation and, therefore, the development of the ability to alter one's responses, one of the characteristics associated with the human condition (Baumeister and Heatherton, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo son pocos los estudios que evidencian que mediante programas de trabajo sistemático se puede aumentar y fortalecer la inteligencia emocional del alumnado de primaria (Sotil et al, 2008); una de las razones de ello es que no existen instrumentos de evaluación validados adaptados al nivel del desarrollo de dicho alumnado (Filella-Guiu et al, 2014;Merchán, Bermejo & González, 2014). Pero no cabe duda de que para conseguir un adecuado desarrollo emocional del alumnado es necesario potenciar el desarrollo de las competencias emocionales del profesorado, es decir, por un lado, la necesidad de que dicho profesorado afronte con inteligencia emocional las tareas propias del ejercicio diario de su profesión, y por otro, la necesidad de educar las competencias emocionales de su alumnado (Pérez, Filella, Soldevila & Fondevila, 2013). El profesorado se tiene que convertir en "educadores emocionales", dicho de otro modo, debe tener equilibradas sus propias emociones (Aguayo-Muela & Aguilar-Luzón, 2017).…”
Section: Marco Teóricounclassified
“…A la vez que mejora su propio bienestar personal, su efectividad y calidad a la hora de llevar a cabo los procesos de enseñanza-aprendizaje del aula, en general (Hué, 2012;Palomera et al, 2008;Pérez-Escoda et al, 2013), potenciándose ambientes ricos y positivos de aprendizaje, en particular (Colom y Froufe, 2001;Pérez-Escoda et al, 2013).…”
Section: Ainoa Martínez Sánchezunclassified
“…Que, a través de sus experiencias, puedan enseñar a reconocer, controlar y expresar respetuosa y claramente sus emociones, ya que los beneficios educativos son numerosos. Por ejemplo: el clima del aula, generado por la actuación del maestro, impactará definitivamente en el aprendizaje de los alumnos (Buitrón y Navarrete, 2008;López, 2012;Palomera et al, 2008); surtirá un efecto positivo en el ambiente del aula lo que a su vez redunda en un mayor bienestar de los alumnos/as y en menores niveles de estrés y frustración, mayor atención y una conducta mejor (Lantieri y Nambiar, 2012); disminución del número de expulsiones de clase, el índice de agresiones y el absentismo escolar, así como en la mejora de las calificaciones académicas y el desempeño escolar (Collaborative for Academic, Social and Emotional Learning, 2003;Pérez-Escoda et al, 2013); igualmente, la educación socio-emocional aumenta el aprendizaje de estas áreas del desarrollo y el aprendizaje académico en los estudiantes (Palomera et al, 2008), así como posibilita un ambiente escolar más armonioso (Pérez-Escoda, Filella, Alegre y Bisquerra, 2012).…”
Section: Ainoa Martínez Sánchezunclassified